ZOOPLANKTON DISTRIBUTION FROM BACKSCATTER DATA OF ADCP INSTRUMENT IN WEST SUMATRA WATERS - Napitupulu, Gandhi; Farihah, Rizqi Ayu; Manik, Henry Munandar; Larasati, Oktavira Dwi Demia; Napitupulu, Moses; Bernawis, Lamona Irmudyawati; Radjawane, Ivonne Milichristi; Kusmanto, Edi (BULLETIN OF THE MARINE GEOLOGY, 2024)
Acoustic Doppler Current Profiler (ADCP) conventionally used to monitor ocean current profiles and potentially detect zooplankton distribution remains largely unexplored. Zooplankton are key consumers in the marine food chain, therefore understanding their distribution is critical. This study aims to map the distribution of zooplankton in West Sumatra waters using ADCP backscatter data. Data analyzed encompass ocean current measurements, backscatter, and conductivity-temperature-depth (CTD) profiles collected from March 1 to 3, 2017. Raw ADCP digital counts were converted into mean volume backscattering strength (MVBS) in dB using sonar equations, proportional to zooplankton biomass. The conversion process involved corrections for sound attenuation due to distance and water absorption, ADCP transducer angle correction, and noise correction. Processing results revealed zooplankton distribution in raw ADCP data ranging from 20 to 160 counts and in MVBS data spanning -140 dB to -40 dB. MVBS values derived from ADCP acoustic signal processing were filtered within the -100 dB to -60 dB range, representing the zooplankton backscatter range. Zooplankton distribution was observed at depths of 0-300 m. Vertical zooplankton distribution was generally high in the 100-200 m layer and decreased at 0-100 m and 200-300 m. This is attributed to the influence of the Equatorial Undercurrent transporting zooplankton biomass from the Indian Ocean to West Sumatra waters at depths of 100-200 m, characterized by high salinity (34.6-35.2 PSU) and cold temperatures (19°-21°C). This study demonstrates the utility of ADCP in observing zooplankton distribution based on their backscatter values and the influence of ocean currents in transporting zooplankton biomass.